Xiphinema italiae Meyl, 1953 (Nematoda: Longidoridae) from Montenegro, and comments on the number of juvenile developmental stages in this species - Barsi, László (Biologia Serbica, 2024)
In May 2006, a population of Xiphinema italiae was found in sandy soil in the rhizosphere of black pine (Pinus nigra Arnold) on Velika plaža, a sandy beach in Ulcinj (Montenegro). This population is briefly described, illustrated and the morphometric data of females and four juvenile developmental stages (JDS) are presented, in order to contribute to the knowledge of the intraspecific variability of this species. Based on the available literature data, it was determined that the morphometry of the populations of X. italiae shows a wide range of intraspecific variability. Data on the developmental biology of X. italiae show the existence of populations with three or four JDS. This discrepancy of data from the literature on the number of JDS in X. italiae prompted me to analyze the situation in a little more detail. The results of data analysis regarding the number of juvenile stages in X. italiae are presented in this paper.